Pengembangan Kurikulum Pendidikan Islam Era Society 5.0 - Abdul Haris (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2023)
This paper is intended to organize a comprehensive understanding in the development of the Islamic education curriculum so that an organized curriculum is obtained in an integrated manner between its components in an adequate operational standard. With the hope that the curriculum is able to form a true Muslim personality. The writing method uses literature review, then is analyzed descriptively and argumentatively. In developing the Islamic education curriculum in the Society 5.0 era, it should be done proportionally and not get stuck in the character or learning model of the 21st Century and the concept of independent learning. The development of an Islamic education curriculum does not necessarily welcome the paradigm and standard of the 21st Century learning process which absolutely requires high-level thinking skills. The success of learning Islamic education is not only measured by the ability to think analytically, critically and creatively. Learning Islamic education requires the ability to think as a whole and thoroughly, without dichotomizing high-level thinking skills with low-level thinking skills. In order to understand and learn the main points of Islamic teachings, it is necessary to involve the ability (to think) to know, understand, live, believe, to then believe in and practice according to instructions originating from the Al-Qur'an and Hadits. In forming a true Muslim personality, it is absolutely necessary to have the ability to think in a realm which, according to the paradigm of thinking in this century, belongs to the realm of low-order thinking skills or what is called Low Order Thinking Skills (LOTS).